Investigating fat reduction absorption and sensory properties for Kubeh during deep frying using carob as coating films - Angor, Malak (Frontiers in Sustainable Food Systems, 2023)
The present study evaluated the impact of carob-based coating films on Fat %, moisture %, fat uptake %, moisture retention %, and sensory scores of Kubeh during deep-fat frying. Various coating solutions using carob (seeds, fruit, and a combination of seeds and fruit) were heated to 80°C for 15 min, followed by cooling. The Kubeh samples were then immersed in the coating solutions and allowed to air dry. The treated samples were subsequently subjected to deep-fat frying, and their moisture retention, ash content, and fat absorption were analyzed, also fat uptake and moisture retention were calculated. Additionally, sensory evaluations were conducted to assess the perceived attributes. The results demonstrated that all the carob-based coating treatments exhibited reduced fat absorption during deep-fat frying. Among the different coating films, those derived from carob seeds were the most effective in minimizing fat absorption. The coating films made from carob fruit also demonstrated a significant reduction in fat absorption compared to the control samples. Moreover, the combination of carob seeds and fruit in the coating film exhibited an intermediate level of fat absorption reduction. Furthermore, all the carob-coated Kubeh samples exhibited an improvement in sensory attributes, unlike the control group. The sensory evaluations exhibited a positive impact of carob coatings on the overall sensory experience of Kubeh.